Genome-Wide Identification and Comparative Analysis of ARF Family Genes in Three Apiaceae Species - Pei, Qiaoying; Li, Nan; Yang, Qihang; Wu, Tong; Feng, Shuyan; Feng, Xuehuan; Jing, Zange; Zhou, Rong; Gong, Ke; Yu, Tong; Wang, Zhen; Song, Xiaoming (Frontiers in Genetics, 2021)
The family Apiaceae includes many important vegetables and medicinal plants. Auxin response factors (ARFs) play critical roles in regulating plant growth and development. Here, we performed a comprehensive analysis of the ARF gene family in three Apiaceae species, celery, coriander and carrot, and compared the results with the ARF gene family of lettuce, Arabidopsis and grape. We identified 156 ARF genes in all six species and 89 genes in the three Apiaceae species, including 28, 34 and 27 in celery, coriander and carrot, respectively. The paralogous gene number in coriander was far greater than that in carrot and celery. Our analysis revealed that ARF genes of the three Apiaceae species in 34 branches of the phylogenetic tree underwent significant positive selection. Additionally, our findings indicated that whole-genome duplication played an important role in ARF gene family expansion. Coriander contained a greater number of ARF genes than celery and carrot because of more gene duplications and less gene losses. We also analyzed the expression of ARF genes in three tissues by RNA-seq and verified the results by quantitative real-time PCR. Furthermore, we found that several paralogous genes exhibited divergent expression patterns. Overall, this study provides a valuable resource for exploring how ARF family genes regulate plant growth and development in other plants. Since this is the first report of the ARF gene family in Apiaceae, our results will serve as a guide for comparative and functional analyses of ARF and other gene families in Apiaceae.